Design, Analysis and Optimization of a Solar Dish/Stirling System - Seyyed Danial Nazemi; Mehrdad Boroushaki (International Journal of Renewable Energy Development, 2016)
In this paper, a mathematical model by which the thermal and physical behavior of a solar dish/Stirling system was investigated, then the system was designed, analysed and optimized. In this regard, all of heat losses in a dish/Stirling system were calculated, then, the output net-work of the Stirling engine was computed, and accordingly, the system efficiency was worked out. These heat losses include convection and conduction heat losses, radiation heat losses by emission in the cavity receiver, reflection heat losses of solar energy in the parabolic dish, internal and external conduction heat losses, energy dissipation by pressure drops, and energy losses by shuttle effect in displacer piston in the Stirling engine. All of these heat losses in the parabolic dish, cavity receiver and Stirling engine were calculated using mathematical modeling in MatlabTM software. For validation of the proposed model, a 10 kW solar dish/Stirling system was designed and the simulation results were compared with the Eurodish system data with a reasonable degree of agreement. This model is used to investigate the effect of geometric and thermodynamic parameters including the aperture diameter of the parabolic dish and the cavity receiver, and the pressure of the compression space of the Stirling engine, on the system performance. By using the PSO method, which is an intelligent optimization technique, the total design was optimized and the optimal values of decision-making parameters were determined. The optimization has been done in two scenarios. In the first scenario, the optimal value of each designed parameter has been changed when the other parameters are equal to the designed case study parameters. In the second scenario, all of parameters were assumed in their optimal values. By optimization of the modeled dish/Stirling system, the total efficiency of the system improved to 0.60% in the first scenario and it increased from 21.69% to 22.62% in the second scenario of the optimization, while the system variables changed slightly. Article History: Received Sept 28, 2015; Received in revised form January 08, 2016; Accepted February 15, 2016; Available online How to Cite This Article: Nazemi, S. D. and Boroushaki, M. (2016) Design, Analysis and Optimization of a Solar Dish/Stirling System. Int. Journal of Renewable Energy Development, 5(1), 33-42. http://dx.doi.org/10.14710/ijred.5.1.33-42